Analisis Kebutuhan Pengembangan Modul dengan Model Make a Match Berbasis Digital Daily Assasment: Analysis of Module Development with Make a Match Model Based on Digital Dairy - Prasmala, Erfitra Rezqi; Tanggu, Emirensiana D. (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to analyze whether or not modules need to be developed with a match-match learning model based on Digital Daily Assessment. This research is a defining stage in development research, carried out by distributing needs analysis questionnaires to students and teachers in Paramitha Islamic Middle School Malang. Based on the results of the questionnaire showed that the module needs to be developed with a Match Daily model based on Digital Daily Assistance.